2019
DOI: 10.1111/jam.14234
|View full text |Cite
|
Sign up to set email alerts
|

Active prokaryotic population dynamics exhibit high correlation to reactor performance during methane production from acid hydrolysates ofAgave tequilanavar.azulbagasse

Abstract: Aims The purpose of this study was to apply cDNA approach for the characterization of active prokaryotic community to understand microbial scenarios and performance of an AnSBR digester fed with acid hydrolysates of Agave tequilana var. azul bagasse (ATAB). Methods and Results The digester was implemented for methane production under organic loading rate (OLR) disturbances to correlate physicochemical variables with changes in abundance, diversity and population dynamics of active Bacteria and Archaea by princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…It has been previously observed that the two-stage AD of TV at low concentrations of VFAs (low OLRs) favored the acetoclastic pathway, in contrast, hydrogenotrophic methanogens enriched at high concentrations (high OLRs) [7]. This change in diversity has been also observed in an AnSBR digester fed with acid AB hydrolysates [53]. However, the opposite trend was observed during the single stage AD of TV using a pilot-scale PBR [47].…”
Section: Microbial Communitiesmentioning
confidence: 65%
See 1 more Smart Citation
“…It has been previously observed that the two-stage AD of TV at low concentrations of VFAs (low OLRs) favored the acetoclastic pathway, in contrast, hydrogenotrophic methanogens enriched at high concentrations (high OLRs) [7]. This change in diversity has been also observed in an AnSBR digester fed with acid AB hydrolysates [53]. However, the opposite trend was observed during the single stage AD of TV using a pilot-scale PBR [47].…”
Section: Microbial Communitiesmentioning
confidence: 65%
“…However, the opposite trend was observed during the single stage AD of TV using a pilot-scale PBR [47]. Regardless of the tequila by-product used, loss of syntrophic relationships for interspecies H 2 /HFor transfer and interspecies HAc transfer has been associated with microbial imbalance, which subsequently affects negatively bioCH 4 production [8,53]. However, in the case of multi-stage AD processes, unsuitable concentrations of hydrolytic/acidogenic bacteria in DF effluent may be quite detrimental for the granular methanogenic sludge [15].…”
Section: Microbial Communitiesmentioning
confidence: 99%
“…The methane yield obtained with this type of hydrolysates is similar to other reports using specialized reactors or similar hydrolysates. 41,42 Interestingly, the [Ch][Lys]-pretreated solids without being saccharied reached 433 mL of methane with a yield of 0.24 L CH 4 per VSS, representing a 5.4 fold compared to the untreated ATB and a 70% of the methane produced by the hydrolysate; making clear that the availability of the nutrients contained in the ATB increases considerably through pretreatment with ILs.…”
Section: Optimization Of the Pretreatment Conditionsmentioning
confidence: 99%
“…6 Methanosaetaceae represents only 3.2%. 55 Moreover, the metabolic activity through RNA-based analysis 56 can provide a more precise visualization of short-term dynamics of CH 4 producing population in further studies. The relative abundance of the main phylogenetic groups found within the archaeal domain, which is in accordance with the data from the rrs sequence analysis, confirms the presumable capability of the primers used for the phylogenetic classification to amplify the 16S rRNA gene sequences of the Archaea without preference or discrimination of single subgroups.…”
Section: Real-time Pcr Based Analysismentioning
confidence: 99%
“…Since the number of operons coding for the 16S RNA gene can vary considerably from species to species and even within strains, moderate differences can be observed between the actual and the investigated relative abundances of microorganisms. 55 Moreover, the metabolic activity through RNA-based analysis 56 can provide a more precise visualization of short-term dynamics of CH 4 producing population in further studies.…”
Section: Real-time Pcr Based Analysismentioning
confidence: 99%